Negotiating access and buy-in from communities in the context of a South African combination HIV prevention intervention for adolescent girls and young women - Armien, Rizqa (Department of Public Health and Family Medicine, 2020)
Background: In response to the persistently high incidence of HIV in adolescent girls and young women in South Africa, the Global Fund invested in a combination HIV prevention intervention aimed at adolescent girls and young women in 10 high priority districts. The HERStory study evaluated the combination HIV prevention intervention after two years of implementation. Using the findings of the HERStory evaluation, this study aims to contribute towards the literature related to understanding factors related to successfully accessing communities and gaining community buy-in or support for community based interventions. The HERStory study explored the identification of the gaps and challenges in the intervention components and the intervention implementation to be able to revise and improve the intervention and its implementation. Methods: In-depth interviews and focus group discussions with community leaders, program implementers and intervention facilitators were conducted. The data consisted of 32 transcripts; a subset of the qualitative data collected for the HERStory evaluation. The analysis for this study sought to better understand the barriers and facilitators of community access and the importance of community buy-in using the HERStory evaluation. Thematic analysis of the data was conducted, supported by Nvivo 12 qualitative data analysis software. Results: The main themes of this secondary analysis were 1) the complexity of negotiating access to communities through key stakeholders, 2) challenges to gaining buy-in, and 3) facilitators and barriers to community based intervention implementation. There were clear facilitators to community access and intervention buy-in such as creating clear communication lines between stakeholders and scheduling regular meetings. Delayed or rushed community engagement resulted in misunderstandings and was identified as barriers to community access and intervention buy-in. Conclusion: Quality community engagement was essential in the facilitation of access and intervention buy-in to promote successful intervention implementation. Recommendations for future interventions include planning enough time for community engagement throughout the intervention including the design phase and establishing clear and effective communication channels between intervention implementers and community stakeholders.